PERAN MANAJEMEN PEMBIAYAAN DALAM PENYEDIAAN SARANA DAN PRASARANA SEKOLAH - Chairun Nisa Male; Okta Iwan Setiawan; Iis Susanti; Subandi; Amiruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the role of financial management in the provision of school facilities and infrastructure. The research employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The research subjects consisted of the principal, school treasurer, and parties involved in managing educational facilities and infrastructure. The results showed that financial management plays an important role in supporting the provision of educational facilities through planning, implementation, supervision, and evaluation of school fund utilization. Proper financial management helps schools determine priority needs for facilities and infrastructure so that the learning process can run more effectively and conducive. However, several obstacles were still found in its implementation, such as limited budgets, delays in fund disbursement, and the incomplete fulfillment of school facility needs. In addition, cooperation among schools, the government, and the community became an important factor in supporting the development of educational facilities and infrastructure. Based on the findings, it can be concluded that effective, transparent, and well-planned financial management can improve the provision of school facilities and infrastructure, thereby supporting the improvement of educational quality.